Respuesta :

g(x)=2x+1
g(3)=2(3)+1
g(3)=6+1
g(3)=7

Answer: The value of [tex]g(3) = 7[/tex]

Step-by-step explanation:

The given function : [tex]g(x) = 2x + 1.[/tex]

We know that to calculate the value of f(a), where f(x) be any function , we need to substitute the value of x=a in the function.

To calculate the value of g(3) , we need to substitute the value of x=3 in the above function , we get

[tex]g(3)=2(3)+1\\\\\Rightarrow\ g(x3=6+1\\\\\Rightarrow\ g(3)=7[/tex]

Therefore, we get the value of [tex]g(3) = 7[/tex]